Política de interiorização do ensino superior: o caso da Universidade Federal de Sergipe - Oliveira Junior, Vanyldo Bernardino de (2016)
The Brazilian higher education has been passing trough an intense expansion process. Public policies intended to the growth of enrollment number and universities are being implemented since 2004, period when the federal government started the Expandir program. Looking to democratize the public university on the most efficient way, the federal government tried, as a priority, decentralize the higher education institutions. The Federal University of Sergipe, on the other hand, started its expansion on 2006, with the creation of an unity at the east of the state. Nowadays, the university has four campuses decentralized and thirteen sites of distance learning in different locations. The creation of decentralized campuses implies on new demands and challenges for the institution, therefore, the monitoring of this process on its different dimensions allow the management to be able to identify the elements witch needs improvements and the reapply of the better practices. Methodologically, the research was realized by a case study with the objective of analyze the conditions involved on the decentralization process of the Federal University of Sergipe. About its nature, the research classifies as descriptive, the data collect was made by documental research and interviews with the majors executives involved on the management and creation of the decentralized campuses. During the realization of the organizational diagnosis it was found some administrative dysfunctions capable to prejudice the management development on the analyzed campuses, it was also verified some bad performances on academic indicators. Moreover it was identified the need of adjusts on some physical structures, what it is an obstacle to the academic evolution of the university on the countryside from the state. Lastly, it is presented an action plan with the objective to mitigate these negative reflexes faced by the executives who work on the decentralized campuses from the university.